The Enduring Principles: Modern Relevance of Governance in Amish Tripathi’s Ram Chandra Series (Journal of Advances and Scholarly Researches in Allied Education, 2020)
Contemporary mythological fiction has emerged as an important literary genre that reinterprets ancient narratives for modern readers. Amish Tripathi, through his Ram Chandra Series, presents not merely a retelling of the Ramayana but a thoughtful exploration of governance, leadership, justice, and ethical responsibility. This research paper examines the modern relevance of governance principles depicted in the series and analyzes how Tripathi adapts ancient ideals to address contemporary political and social concerns. Through the portrayal of Rama’s leadership, the paper explores themes such as rule of law, public welfare, ethical leadership, accountability, communication, and the balance between tradition and modernity. The study argues that Tripathi’s reinterpretation of epic governance offers valuable insights into present-day administrative and political systems. By blending mythology with modern sensibilities, the series highlights the timeless relevance of responsible leadership and just governance in contemporary society.